2016
DOI: 10.1371/journal.pone.0165290
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Relevant Neuroinflammation Mechanisms Using Gene Expression Profiling in Patients with Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by damage of motor neurons. Recent reports indicate that inflammatory responses occurring within the central nervous system contribute to the pathogenesis of ALS. We aimed to investigate disease-specific gene expression associated with neuroinflammation by conducting transcriptome analysis on fibroblasts from three patients with sporadic ALS and three normal controls. Several pathways were found to be upregulated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…More and more studies point to the role of systemic inflammation and immune response in ALS patients [11][12][13]. It has been shown that in ALS, microglia and astrocytes are activated, which is neuroprotective in the early stages of the disease and proinflammatory in the later stages.…”
Section: Inflammatory Pattern Of Expression In a Group Of Patients Analysis Of Heat Maps And Volcano Plots Of Neuroinflammatory Gene Exprmentioning
confidence: 99%
“…More and more studies point to the role of systemic inflammation and immune response in ALS patients [11][12][13]. It has been shown that in ALS, microglia and astrocytes are activated, which is neuroprotective in the early stages of the disease and proinflammatory in the later stages.…”
Section: Inflammatory Pattern Of Expression In a Group Of Patients Analysis Of Heat Maps And Volcano Plots Of Neuroinflammatory Gene Exprmentioning
confidence: 99%
“…It is increased in serum and CSF of sALS patients [34]. CCL1 is secreted by the monocytes or macrophages in response to LPS exposure to promote the NF-κB pathway, and CXCL1 is also implicated in NF-κB activation through the PI3K/AKT signaling pathway and is also increased in ALS patient’s fibroblasts [35, 36]. We have previously reported that UBQLN2 up-regulation can activate the NF-κB signaling pathway [12].…”
Section: Resultsmentioning
confidence: 99%
“…CXCL1 is a chemotactic cytokine responsible for mediating migration of neutrophils to the site of inflammation 2629 and previous studies have demonstrated a significant increase in CXCL1 levels in ALS 29,30 . Specifically, CXCL1 levels were increased in monocytes isolated from ALS patients 29 and in ALS patient-derived fibroblasts 30 . Here, we demonstrate that CXCL1 levels are increased in the spinal cord of TgSOD1 mice similar to previous reports in ALS patients, however, its role in ALS pathogenesis is yet unclear.…”
Section: Discussionmentioning
confidence: 99%